(untitled) (International Journal of Engineering and Computer Science, 2013)
Every software project practices some kind of reuse as a common sense practice. Very often, practitioners use parts of code, documents and experiences from previous projects as a personal initiative. Of course, this kind of reuse brings some benefits to the company. However, it is generally performed in isolation from other projects, depends on the individual’s initiative and has very limited impact. Systematic Software Reuse is the capability of an organization to obtain maximum profit from the experiences acquired in former projects by identifying the reuse opportunities a priori and establishing the appropriate organizational, managerial and budgetary support. Software Reuse reduces development costs and time by avoiding the duplication of work.